Gasoline aromatics: a critical determinant of urban secondary organic aerosol formation - Peng, J. F.; Min* Hu; Du, Z. F.; Wang, Y. H.; Zheng, J.; Zhang, W. B.; Yang, Y. D.; Qin, Y. H.; Zheng, R.; Xiao, Y.; Y.S. Wu; Lu, S. H.; et al. (Atmospheric Chemistry and Physics, 2017)
Gasoline vehicle exhaust is an important contributor to secondary organic aerosol (SOA) formation in urban atmosphere. Fuel composition has a potentially considerable impact on gasoline SOA production, but the link between fuel components and SOA production is still poorly understood. Here, we present chamber experiments to investigate the impacts of gasoline aromatic content on SOA production through chamber oxidation approach. A significant amplification factor of 3-6 for SOA productions from gasoline exhausts is observed as gasoline aromatic content rose from 29 to 37 %. Considerably higher emission of aromatic volatile organic compounds (VOCs) using high-aromatic fuel plays an essential role in the enhancement of SOA production, while semi-volatile organic compounds (e.g., gas-phase PAHs) may also contribute to the higher SOA production. Our findings indicate that gasoline aromatics significantly influence ambient PM2.5 concentration in urban areas and emphasize that more stringent regulation of gasoline aromatic content will lead to considerable benefits for urban air quality.
Keywords: black carbon; carbon particles; China; combustion; evolution; particulate matter emissions; regional receptor-site; smog chamber; Transport; vehicle emissions